2020
DOI: 10.3390/cells9040809
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Metabolic Flexibility in the Osteoarthritis Process: A Study on Transmitochondrial Cybrids

Abstract: Osteoarthritis (OA) is the most frequent joint disease; however, the etiopathogenesis is still unclear. Chondrocytes rely primarily on glycolysis to meet cellular energy demand, but studies implicate impaired mitochondrial function in OA pathogenesis. The relationship between mitochondrial dysfunction and OA has been established. The aim of the study was to examine the differences in glucose and Fatty Acids (FA) metabolism, especially with regards to metabolic flexibility, in cybrids from healthy (N) or OA don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…[ 23 ] A recent study reported that degeneration of cartilage may be triggered by metabolic disorders of glucose balance. [ 10 , 24 , 25 ] RA is a chronic systemic autoimmune disease featured with painful joint inflammation and disability. The changes in glucose metabolism are believed to contribute to disease progression of RA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] A recent study reported that degeneration of cartilage may be triggered by metabolic disorders of glucose balance. [ 10 , 24 , 25 ] RA is a chronic systemic autoimmune disease featured with painful joint inflammation and disability. The changes in glucose metabolism are believed to contribute to disease progression of RA.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past decade, evidence has accumulated that there is an association between mtDNA haplogroups and the prevalence, progression and incidence of the disease 14 19 . This link has been assessed only in ex vivo studies and only with the use of in vitro transmitochondrial cybrid models 20 . Thus, the causal link between mtDNA haplotype variability and OA joint phenotype has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Co‐evolution and interaction between both genomes make it difficult to consolidate the association studies. The effects of polymorphic mtDNA excluding the divergence effects from the nDNA were first described in transmitochondrial cybrid cell lines 67–71 and then using mouse models carrying different mtDNA species under a common nuclear background 72–79 . The use of transmitochondrial cybrids has been extensively used to understand mtDNA‐nDNA compatibility as an in vitro model to study the effects of having different mtDNA species under the same nuclear background 80 .…”
Section: Co‐evolution Of Genomesmentioning
confidence: 99%
“…Better cell survival under mtDNA haplotype J was associated with a downregulation of the expression of the proapoptotic gene BBC3 70 . Further analyses using a supplementary haplotype N showed that fatty acid oxidation decreased under mtDNA variants J and H in comparison with N in OA cybrid models 71 . For decades, efforts to validate mtDNA variants and their role in different diseases were made to identify‐specific treatment and diagnosis approaches.…”
Section: Co‐evolution Of Genomesmentioning
confidence: 99%